Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1002/glia.24346
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum associated degradation is essential for maintaining the viability or function of mature myelinating cells in adults

Abstract: Endoplasmic reticulum associated degradation (ERAD) is responsible for recognition and degradation of unfolded or misfolded proteins in the ER. Sel1L is essential for the ERAD activity of Sel1L-Hrd1 complex, the best-known ERAD machinery. Using a continuous Sel1L knockout mouse model (CNP/Cre; Sel1L loxP/loxP mice), our previous studies showed that Sel1L knockout in myelinating cells, oligodendrocytes in the central nervous system (CNS) and Schwann cells in the peripheral nervous system (PNS), leads to adult-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 51 publications
(150 reference statements)
0
1
0
Order By: Relevance
“…XBP1s appears to exert its protective function mostly via up-regulation of genes involved in ER proteostasis pathways such as ERAD. This is particularly intriguing since we and others have recently shown that a functional ERAD is required to maintain myelin in adult glial cells, 56,58 and that impairment of ERAD severely worsens myelin defects and neurophysiological parameters in CMT1B. 56 Mutant misfolded P0 proteins are in fact degraded via the ERAD-proteasome pathway, 56,59 and impairment of ERAD via Schwann cell specific ablation of Derlin-2 exacerbated the UPR and the overall phenotype of S63del mice.…”
Section: Xbp1 Is Protective In Different Models Of Proteotoxic Cmt1bmentioning
confidence: 98%
“…XBP1s appears to exert its protective function mostly via up-regulation of genes involved in ER proteostasis pathways such as ERAD. This is particularly intriguing since we and others have recently shown that a functional ERAD is required to maintain myelin in adult glial cells, 56,58 and that impairment of ERAD severely worsens myelin defects and neurophysiological parameters in CMT1B. 56 Mutant misfolded P0 proteins are in fact degraded via the ERAD-proteasome pathway, 56,59 and impairment of ERAD via Schwann cell specific ablation of Derlin-2 exacerbated the UPR and the overall phenotype of S63del mice.…”
Section: Xbp1 Is Protective In Different Models Of Proteotoxic Cmt1bmentioning
confidence: 98%